PENGARUH LIKUIDITAS DAN RASIO EFISIENSI TERHADAP HARGA SAHAM YANG DIMEDIASI KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dyah Nurul Bayu Pertiwi; Sarbullah Sarbullah (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract The purpose of this study is to empirically examine: 1) the effect of liquidity and efficiency ratios on financial performance in banking companies listed on the IDX; 2) the effect of liquidity and efficiency ratios on stock prices in banking companies listed on the IDX; 3) the influence of financial performance on stock prices in banking companies listed on the IDX; 4) the influence of liquidity on stock prices with financial performance as a mediating variable in banking companies listed on the IDX; and 5) the effect of the efficiency ratio on stock prices with financial performance as a mediating variable in banking companies listed on the IDX. The research sample is in accordance with predetermined criteria as many as 27 banking sector companies that go public, using the pooling data method or a combination of time series data and cross section data for 2012-2016, so that if you add up there are 135 samples (n). The results of the study show that: 1) Liquidity has a significant effect on financial performance, so that hypothesis 1 is accepted; 2) The efficiency ratio has no significant effect on financial performance, so hypothesis 2 is rejected; 3) Liquidity has a significant effect on stock prices, so hypothesis 3 is accepted; 4) The efficiency ratio has a significant effect on stock prices, so hypothesis 4 is accepted; 5) Financial performance has a significant effect on stock prices, so hypothesis 5 is accepted; 6) Liquidity affects stock prices with financial performance as a mediating variable, so hypothesis 6 is accepted; and 7) The efficiency ratio has no effect on stock prices with financial performance as a mediating variable, so hypothesis 7 is rejected.